2015
DOI: 10.15537/smj.2015.9.12118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2 novel homozygous mutations in the methylmalonyl-CoA mutase gene in Saudi patients

Abstract: The aim of this report is to analyze the clinical features, and mutations of the methylmalonyl CoA mutase (MUT) gene in 2 patients with methylmalonic aciduria (MMA) attending King Saud University Medical City, Riyadh, Saudi Arabia in January 2014. The infants aged 6 days (patient 1) and 3 months (patient 2) with sepsis-like picture, metabolic acidosis, and hyperammonemia were presented. Investigations revealed high propionylcarnitine (C3), elevated urinary methylmalonic acids, 3-hydroxypropionic acids and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Kumari, et al, identified 23 novel mutations within exons 2, 9, 11, and 12 of MUT gene among Indian patients [6]. Among Saudi patients, p.Y110C and p.Q734X were found [14]. Ahmadloo, et al, reported a novel variation in the MUT intron 12 (c.2125-3C > G) among Iranian cases with MMA [15].…”
Section: Introductionmentioning
confidence: 99%
“…Kumari, et al, identified 23 novel mutations within exons 2, 9, 11, and 12 of MUT gene among Indian patients [6]. Among Saudi patients, p.Y110C and p.Q734X were found [14]. Ahmadloo, et al, reported a novel variation in the MUT intron 12 (c.2125-3C > G) among Iranian cases with MMA [15].…”
Section: Introductionmentioning
confidence: 99%